2020
DOI: 10.1039/c9ta10222a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of bifunctional BaFe1−xCoxO3−y−δ(OH)y catalysts for the oxygen reduction reaction and oxygen evolution reaction

Abstract: Perovskite oxides with mixed ionic and electronic conductivities are very promising candidates for their application as energy materials related to fuel cell and metal air battery integration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…The reason for different expansion properties could be the higher Fe content and the related higher lattice parameter for presented in this work BFCN. Waidha et al [52] analysed water incorporation to BaFe 1-x Co x O 3-d structures and observed that the amount of water the sample can incorporate (and at the same time the possibilities of related negative thermal expansion upon heating and water release) strongly depends on the Fe:Co proportion. It was reported that the basicity of the oxide ions is another key parameter for water incorporation [15].…”
Section: Effect Of Temperature On Thermal Expansion and Mass Changementioning
confidence: 99%
“…The reason for different expansion properties could be the higher Fe content and the related higher lattice parameter for presented in this work BFCN. Waidha et al [52] analysed water incorporation to BaFe 1-x Co x O 3-d structures and observed that the amount of water the sample can incorporate (and at the same time the possibilities of related negative thermal expansion upon heating and water release) strongly depends on the Fe:Co proportion. It was reported that the basicity of the oxide ions is another key parameter for water incorporation [15].…”
Section: Effect Of Temperature On Thermal Expansion and Mass Changementioning
confidence: 99%
“…The solvent-free membrane preparation has been chosen as garnets are known to undergo Li + /H + exchange, which can affect its intrinsic Li-ion conductivity . The ceramic garnet particles are synthesized via nebulized spray pyrolysis (NSP), which has been reported to provide particles with high surface area compared to solid-state synthesis routes due to significant lowering of annealing temperatures and times, with particle sizes in the range of ∼1 μm and below. Although nanoparticles have been the choice of the filler and are known to increase the conductivity of the polymer-rich composites, the garnet particles chosen in this study aim to be a compromise for providing sufficient surface area for ceramic–polymer interactions while maintaining longer conductive pathways within the ceramic particles (which have a higher grain conductivity than the polymer) due to their larger sizes.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the basicity of dopant ions, the water incorporation can vary; Waidha et al found that the Co/Fe ratio significantly affects the water incorporation level, when Co and Fe are co-doped in similar perovskites. 41,42 Here, we observe that the plateau caused by dehydration decreases in extent and shifts to lower temperatures with increasing Co content. This is consistent with the studies cited above demonstrating that both the proton content and dehydration temperature in mixed Co/Fe-containing proton conducting oxides decreases with increasing Co content.…”
Section: Resultsmentioning
confidence: 58%